Strengthening Land Administration Governance Through Electronic Land Certificates for Bureaucratic Reform at The Medan City Land Office - Enos Bonar Hasudungan Lumban Tobing; Fitri Rafianti; Dahlan Dahlan (Utan Kayu Publishing, 2025)
The implementation of land administration reforms through electronic land certificates presents a critical challenge in bridging the gap between normative legal frameworks and factual bureaucratic practice in Indonesia. This thesis examines the strengthening of land administration governance through electronic land certification at the Medan Land Office, with particular emphasis on its implications for bureaucratic reform. Employing socio-legal research methodology through qualitative inquiry, the study identifies a significant phenomenon termed